Biochemical Aspects and Risk Factors Associated with Cervical Cancer - Janet Villafuerte Reinante; Yoel Hernández Guerra; Zuria Elisa Ayala Reina; Laura Naranjo Hernández; José Ángel González Alonso; Mirialys Brito Méndez (Revista Finlay)
Cervical cancer is among the leading causes of women´s death, which is a serious problem for health. It has been demonstrated, through epidemiological studies, that its main risk factor is infection by human papillomavirus. There are other host factors that predispose women for developing cancer of the cervix. The slow evolution of the disease and the accessibility of the cervix for its study, allow time and tools to detect and eradicate the disease. Knowing the biochemical aspects in its genesis could contribute to the search for more effective detection and treatment methods in malignant lesions of the cervix. A bibliographic review was carried out with the objective of describing a general panorama about the biochemical aspects and the risk factors associated with this type of cancer. The scientific databases were consulted: Pubmed, Biomed Central, Medline, Scielo and Academic Google.